PENGARUH LOYALITAS, KOMITMEN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA BIRO HUMAS DAN KEPROTOKOLAN SEKRETARIAT DAERAH PROVINSI SUMATERA UTARA - Dessy Wahyuni (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
This research aims to find out the influence jointly or partially between loyality, commitment and organizational culture to the performance of the Workers at the Public Relations and Protocol Bureau Regional Secretariat Of North Sumatera. This research uses descriptive qualitative method using primary and secondary data. The population is the workers of the company. Sixty five workers become the sample of this research. Data analysis technique used is linear regression which shows that from the three independent variables applied to the regression model (loyality, commitment and organizational culture). Loyality is significant for 0,073 which can be concluded that loyality not affects performance (hypothesis 1 rejected). Commitment has significant value 0,000 which can be concluded that commitment affects performance (hypothesis 2 accepted). Organizational culture variable has significant value 0,002 which means that organizational culture affects performance (hypothesis 3 accepted). Research results show that loyality, commitment and organizational culture all positively influence the performance of the workers. It can be proven using the result of regression statistic test with probability value 0,000 obtained which is lower than α (α=0,05). So, it can be said that loyality, commitment and organizational culture influence positively the performance of the workers. Thus, hypothesis 4 accepted.